Pengaruh Penggunaan Metode Mind Mapping terhadap Keterampilan Menulis Teks Narasi Siswa Kelas VII UPT SPF SMP Negeri 27 Makassar - Mutmainna Darwis; Kembong Daeng; Nurhusna Nurhusna (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to describe the results of narrative text writing skills before and after using the mind mapping method of grade VII UPT SPF SMP Negeri 27 Makassar, as well as to prove its influence on students' narrative text writing skills. This study uses a type of quantitative research with a pre-experimental design of the one group pre-test post-test. The sample consisted of 31 students obtained from a population of 369 students. The data collection technique was carried out through a test in the form of a writing task, then analyzed using descriptive and inferential statistics. The results showed that the average pre-test score of students was 64 (the least skilled category), while the average post-test score increased to 86 (the highly skilled category). The t-test showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05 which means that there is a significant influence of the use of the mind mapping method on the narrative text writing skills of grade VII students. These findings indicate that the use of mind mapping methods in learning has a positive impact on improving students' comprehension and writing skills.